ARPC1B Mutation Manifesting as Recurrent Hematemesis With Metaplasia. Issue 3 (12th August 2021) - Antala, Swati; Whitehead, Bridget; Melin-Aldana, Hector; Bass, Lee M.
Abstract : ARPC1B is important in the maintenance and assembly of the ARP2/3 complex. Loss of this complex due to ARPC1B mutation results in impairment of actin polymerization and subsequent defects in chemotaxis, cell migration, and DNA repair. Individuals with this rare mutation present in infancy and have abnormal innate and adaptive immune responses. They develop immune-mediated inflammatory disease with associated platelet defects, eosinophilia, rashes, and bowel disease. Recurrent gastrointestinal hemorrhage has been described in known cases. Here, we report a case with endoscopic and histologic findings in a patient with this rare mutation.